2012
DOI: 10.1021/ic2020786
|View full text |Cite
|
Sign up to set email alerts
|

Blue-Emitting Dinuclear N-heterocyclic Dicarbene Gold(I) Complex Featuring a Nearly Unit Quantum Yield

Abstract: Dinuclear N-heterocyclic dicarbene gold(I) complexes of general formula [Au(2)(RIm-Y-ImR)(2)](PF(6))(2) (R = Me, Cy; Y = (CH(2))(1-4), o-xylylene, m-xylylene) have been synthesized and screened for their luminescence properties. All the complexes are weakly emissive in solution whereas in the solid state some of them show significant luminescence intensities. In particular, crystals or powders of the complex with R = Me, Y = (CH(2))(3) exhibit an intense blue emission (λ(max) = 450 nm) with a high quantum yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
91
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(104 citation statements)
references
References 57 publications
12
91
0
1
Order By: Relevance
“…This particular behaviour observed both with chlorine and bromine can be tentatively attributed to the relatively short Au/Au distance in complex 3a (3.27 Å) [17], compared with the other gold(I) cationic complexes (for example 3.54 Å for [Au 2 (MeImeCH 2 eImMe) 2 ](I) 2 ) [18]; DFT calculations are underway to model this reactivity. Furthermore, the coordination mode exhibited by the dicarbene ligands in the Au(II)/Au(II) complex is previously unreported for such ligands.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This particular behaviour observed both with chlorine and bromine can be tentatively attributed to the relatively short Au/Au distance in complex 3a (3.27 Å) [17], compared with the other gold(I) cationic complexes (for example 3.54 Å for [Au 2 (MeImeCH 2 eImMe) 2 ](I) 2 ) [18]; DFT calculations are underway to model this reactivity. Furthermore, the coordination mode exhibited by the dicarbene ligands in the Au(II)/Au(II) complex is previously unreported for such ligands.…”
Section: Discussionmentioning
confidence: 95%
“…The reagents were purchased by Aldrich as high-purity products and generally used as received; all solvents were technical grade and used as received. The gold(I) complexes 1ae5a and PhICl 2 were prepared according to literature procedures [17,19]. NMR spectra (6) Br2eAu2eAu1 179.51 (5) were recorded on a Bruker Avance 300 MHz (300.1 MHz for 1 H and 75.5 for 13 C); chemical shifts (d) are reported in units of ppm relative to the residual solvent signals.…”
Section: General Remarksmentioning
confidence: 99%
“…63,64 These dicarbene chelates are finding widespread use in the preparation of metal complexes suitable for activation of small molecules and as metal catalysts, 65−67 and for making radiopharmaceuticals 68 as well as luminescent materials. 69 On the other hand, the dianionic chelates, namely, 5,5′-di(trifluoromethyl)-3,3′-bipyrazole (bipzH 2 ), was best prepared using Claisen condensation employing ethyl trifluoroacetate and 2,3-butanedione, and subsequent heating with hydrazine at reflux, 53 while 5,5′-di(trifluoromethyl)-3,3′-di-1,2,4-triazole (bitzH 2 ) was obtained from reaction of trifluoroacetamidine and oxalyl dihydrazide, dehydration, and sublimation. Syntheses of bipzH 2 and bitzH 2 have been documented in the literature, 53 while 3-(trifluoromethyl)-5-(4-(trifluoromethyl)phenyl)-1H-pyrazole (phpzH 2 ) was obtained by condensation of 1-(4-(trifluoromethyl)phenyl)ethanone with ethyl trifluoroacetate, followed by hydrazine cyclization.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The synthesis and characterisation of complexes 1 o and 1 m have been already reported by us [7], while complex 1 p is a new compound. In all cases, the formation of the dicarbene complexes is confirmed by the absence of the C2-H signal in the 1 H NMR spectrum of the reaction products, which indicates the deprotonation of the diimidazolium salt, and by the presence of the C2 carbon resonance at about 180 ppm, in a range typical of N-heterocyclic carbenes bonded to Au(I) centres.…”
Section: Resultsmentioning
confidence: 68%
“…We have been interested since some years in the coordination chemistry of N-heterocyclic carbenes and in the catalytic applications of the corresponding Pd(II), Cu(I) and Ag(I) metal complexes [6]. We have also recently shown that Nheterocyclic dicarbenes efficiently coordinate to gold(I) centres [7] and that the resulting [Au 2 (MeIme(CH 2 ) n eImMe) 2 ](PF 6 ) 2 (n ¼ 1e 4) dinuclear complexes can undergo oxidative addition by chlorine or bromine to afford stable and well characterised products [8]. The reaction outcome markedly depends on the length of the alkylene (CH 2 ) n bridge linking the two carbenes moieties, so that with n ¼ 1, 2 and 4 the oxidation with X 2 (X ¼ Cl, Br) gives only the dinuclear bis-dicarbene Au(III)eAu(III) complexes [Au 2 X 4 (MeIme (CH 2 ) n eImMe) 2 ](PF 6 ) 2 , while with the propylene bridging group the major product is the dinuclear Au(II)eAu(II) complex [Au 2 X 2 (MeIme(CH 2 ) 3 eImMe) 2 ](PF 6 ) 2 .…”
Section: Introductionmentioning
confidence: 99%